Research on the speed of light transmission in a dual-frequency laser pumped single fiber with two directions. (8th December 2017) - Qiu, Wei; Liu, Jianjun; Wang, Yuda; Yang, Yujing; Gao, Yuan; Lv, Pin; Jiang, Qiuli
Abstract: In this article a general theory of the coherent population oscillation effect in an erbium-doped fiber at room temperature is presented. We use dual pumping light waves with a simplified two-level system. Thus the time delay equations can be calculated from rate equations and the transmission equation. Using numerical simulation, in the case of dual-frequency pump light waves (1480 nm and 980 nm) with two directions, we analyze the influence of the pump power ratio on the group speed of light propagation. In addition, we compare slow light propagation with a single-pumping light and slow light propagation with a dual-pumping light at room temperature. The discussion shows that a larger time delay of slow light propagation can be obtained with a dual-frequency pumping laser. Compared to previous research methods, a dual-frequency laser pumped fiber with two directions is more controllable. Moreover, we conclude that the group velocity of light can be varied by changing the pump ratio.